2022
DOI: 10.34067/kid.0000352022
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Randomized Controlled Trial of Integrated Palliative Care and Nephrology Care

Abstract: Background: There has been a call by both patients and health professionals for the integration of palliative care with nephrology care, yet there is little evidence describing the impact of this approach. The objective of this paper is to report feasibility and acceptability of a pilot randomized controlled trial testing the efficacy of integrated palliative and nephrology care. Methods: English speaking patients with CKD stage V were randomized to monthly palliative care visits for three months in addition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The need for better access to KSC has been well documented, but efforts to meet the need are nascent. 5 , 41 , 42 Patients with kidney failure have a high symptom burden, a shortened life expectancy, and they experience high intensity care at the end of life compared with patients with other chronic serious illnesses. 43 47 Documented barriers to meeting these KSC needs include training gaps, policies with financial disincentives limiting access to both palliative care and hospice, and resistance to integrating palliative care within the nephrology community because of the misconception that it is synonymous with end-of-life care.…”
Section: Discussionmentioning
confidence: 99%
“…The need for better access to KSC has been well documented, but efforts to meet the need are nascent. 5 , 41 , 42 Patients with kidney failure have a high symptom burden, a shortened life expectancy, and they experience high intensity care at the end of life compared with patients with other chronic serious illnesses. 43 47 Documented barriers to meeting these KSC needs include training gaps, policies with financial disincentives limiting access to both palliative care and hospice, and resistance to integrating palliative care within the nephrology community because of the misconception that it is synonymous with end-of-life care.…”
Section: Discussionmentioning
confidence: 99%
“…An RCT investigating the role of individualized ACP coaching demonstrated that coached patients were more likely to have a documented advanced directive compared with the control group [ 112 ]. Another RCT also showed that monthly palliative care visits in addition to usual nephrology care led to improvement in overall and physical symptoms as well as increased adoption of ACP directives [ 113 ]. However, there are barriers to ACP in CKD patients and their families, including timing issues, concerns about patient and family ailments, limited resources and expertise, difficulties in predicting outcomes, and a lack of shared understanding within nephrology departments regarding the integration of ACP [ 114 ].…”
Section: Palliative Carementioning
confidence: 99%